Keefektifan Model Pembelajaran Example Non-Example Terhadap Hasil Belajar Menulis Deskripsi Siswa Kelas IV SDN Mranggen (Eduscotech, 2022)
Students' ability in writing descriptions is still low. This is because teachers still use the lecture method in their learning so that students quickly get bored and are less interested in learning to write descriptions. Therefore, the author is interested in conducting research with the example non-example learning model to provide an alternative in teaching descriptive writing material. The example non-example learning model uses images as a medium to provide an overview of a situation/activity to students so that they can make a description. Starting from what is in the picture (example), then students are directed to develop their compositions by looking for what situation/activity is not in the picture (non-example). The purpose of this study was to determine the differences in student learning outcomes in classes that apply the example non-example learning model with students in classes that do not apply the example non-example learning model. Based on the independent sample t-test using SPSS version 18, the t count value> t table is 2.498> 1.980 and the significant value is less than 0.05, namely 0.015. The results prove that there is a significant difference and better learning between classes that apply the example non-example learning model compared to classes that do not apply the example non-example learning model. The average learning outcomes of students who apply the example non-example model are 71.32, while the average learning outcomes of students who do not apply the example non-example model are 64.29. This proves that the learning outcomes of students in classes that apply the example non-example model are better than classes that do not apply the example non-example model. From these results, it can be concluded that the application of the example non-example model has proven to be effective in improving student learning outcomes in learning.